Epidural triamcinolone for management of low back pain with radiation- a comparative study of two dose regime (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Low back pain is a very common specially in elderly people. Relief of pain is associated with decrease in morbidity, shorten hospital stay and increase patients satisfaction. Nerve block by epidural steroid and local anaesthetic is an acceptable method to reduce low back pain. Aim and objective: The present study was performed to compare low dose (40 mg) and high dose (80 mg) Triamcinolone to see their effectiveness and side effects in controlling low back pain. Method: This study was a randomized controlled trial. 60 patients with low back pain with radiation, and with positive CT/MRI support has been randomly selected by blind envelop method and divided into two groups, 30 patients in each. Group-A, patients received inj. Triamcinolone (40 mg) and Group-B patients received inj. Triamcinolone (80 mg) epidurally. Results: Both dosage produced effective analgesia in low back pain as assessed by visual analogue scale (VAS) and verbal rating scale (VRS) for the period up to 30 days after administration. Haemodynamic changes showed no significant difference between the two drugs after 30 days. Both drugs produced significant rise of fasting plasma glucose and leucocytosis for the period up to 30 days after administration. Conclusion: Low back pain can be effectively reduced by epidural low dose Triamcinolone (40 mg). DOI: http://dx.doi.org/10.3329/jbsa.v23i1.18153 Journal of BSA, 2010; 23(1): 14-18